ABCDEF Bundle and Supportive ICU Practices for Patients With Coronavirus Disease 2019 Infection: An International Point Prevalence Study. (12th March 2021) - Liu, Keibun; Nakamura, Kensuke; Katsukawa, Hajime; Elhadi, Muhammed; Nydahl, Peter; Ely, Eugene Wesley; Kudchadkar, Sapna R.; Takahashi, Kunihiko; Inoue, Shigeaki; Lefor, Alan Kawarai; Kesecioglu, Jozef; Nishida, Osamu
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: To investigate implementation of evidence-based and supportive cares in ICUs, such as the ABCDEF, nutrition therapy, and ICU diary, for patients with coronavirus disease 2019 infection in ICUs and their association with ICU clinical practice and setting. Design: A worldwide, 2-day point prevalence study. Setting: The study was carried out on June 3, 2020, and July 1, 2020. A total of 212 ICUs in 38 countries participated. Clinicians in each participating ICU completed web-based online surveys. Patients: The ICU patients with coronavirus disease 2019. Interventions: None. Measurements and Main results: The implementation rate for the elements of the ABCDEF bundle, other supportive ICU care measures, and implementation-associated structures were investigated. Data were collected for 262 patients, of whom 47.3% underwent mechanical ventilation and 4.6% were treated with extracorporeal membrane oxygenation. Each element was implemented for the following percentages of patients: elements A (regular pain assessment), 45%; B (both spontaneous awakening and breathing trials), 28%; C (regular sedation assessment), 52%; D (regular delirium assessment), 35%; E (early mobility and exercise), 47%; and F (family engagement and empowerment), 16%. The implementation of element E was 4% for patients on mechanical ventilation and 8% for patients on extracorporeal membrane oxygenation. Supportive care, such as protein provision throughout the ICU stay (under 1.2 g/kg for more than 50% of the patients) and introduction of ICU diary (25%), was infrequent. Implementation rates of elements A and D were higher in ICUs with specific protocols and fewer ICU beds exclusively for patients with coronavirus disease 2019 infection. Element E was implemented at a higher rate in ICUs that had more ICU beds assigned for them. Conclusions: This point prevalence study showed low implementation of the ABCDEF bundle. Specific protocols and the number of ICU beds reserved for patients with coronavirus disease 2019 infection might be key factors for delivering appropriate supportive care.